2010
DOI: 10.2214/ajr.09.3568
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancers Not Detected at MRI: Review of False-Negative Lesions

Abstract: In a population of 220 sequentially diagnosed breast cancer lesions, we found seven (3.2%) MRI-occult cancers, fewer than seen in other published studies. Small tumor size and diffuse parenchymal enhancement were the principal reasons for these false-negative results. Although the overall sensitivity of cancer detection was high (96.8%), it should be emphasized that a negative MRI should not influence the management of a lesion that appears to be of concern on physical examination or on other imaging technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 28 publications
3
37
1
Order By: Relevance
“…Non-mass-like enhancements, such as DCIS lesions, are more difficult to detect in the presence of moderate/marked background enhancement. These results are consistent with those described in previous reports [8][9][10]. Plausible explanations for the lack of adequate breast tumour delineation in breast MRI examinations include differences in histological features, tumour size, and/or the degree of background enhancement [10].…”
Section: Discussionsupporting
confidence: 92%
“…Non-mass-like enhancements, such as DCIS lesions, are more difficult to detect in the presence of moderate/marked background enhancement. These results are consistent with those described in previous reports [8][9][10]. Plausible explanations for the lack of adequate breast tumour delineation in breast MRI examinations include differences in histological features, tumour size, and/or the degree of background enhancement [10].…”
Section: Discussionsupporting
confidence: 92%
“…Focally, asymmetrically or regionally distributed BPE could cause false-positive interpretation, and by contrast, additional malignant foci around the index cancer could be masked by adjacent parenchymal enhancement causing false-negative interpretation. 26,27 The accuracy was significantly lower in patients with moderate or marked BPE causing underestimation or overestimation of lesion extent. 28,29 Our results revealed that of 216 patients with weak BPE, only 21 (10%) patients had positive resection margin, and of 98 patients with strong BPE, 23 (23%) had positive resection margin.…”
Section: Discussionmentioning
confidence: 97%
“…MRI displays high sensitivity for invasive breast cancer (including mammographically occult invasive breast cancer; ref. [31][32][33]; however, its use is limited, by its relatively low sensitivity in the detection of DCIS and low specificity for both invasive carcinoma and DCIS (34)(35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%